2021
DOI: 10.1101/2021.01.02.20248576
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

COVID-19 Pandemic and Behavioural Response to Self-Medication Practice in Western Uganda

Abstract: BackgroundSelf-medication has become is a serious public health problem globally posing great risks, especially with the increasing number of cases of COVID-19 disease in Uganda. This is may be partly because of the absence of a recognized treatment for the disease, however, the prevalence and nature differ from country to country which may influence human behavioural responses.AimThis study aimed to investigated the beharioural response of the community towards self- medication practices during this COVID-19 … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 17 publications
3
18
1
Order By: Relevance
“…Studies characteristics are shown in Table 2 . The eight included studies reported data on self-medication practices in six different countries: three from Peru [ 30 – 32 ], one from Bangladesh [ 33 ], one from Togo [ 29 ], one from Nigeria [ 34 ], one from Uganda [ 35 ], and one from the Kingdom of Saudi Arabia [ 36 ]. All studies were cross-sectional.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies characteristics are shown in Table 2 . The eight included studies reported data on self-medication practices in six different countries: three from Peru [ 30 – 32 ], one from Bangladesh [ 33 ], one from Togo [ 29 ], one from Nigeria [ 34 ], one from Uganda [ 35 ], and one from the Kingdom of Saudi Arabia [ 36 ]. All studies were cross-sectional.…”
Section: Resultsmentioning
confidence: 99%
“…All studies assessed self-medication through self-report. The questions used to assess self-medication were explicitly mentioned only in the one study [ 36 ], while other five studies report having asked for the use of medicine without prescription [ 29 , 31 34 ], and two studies gave no details regarding how self-medication was measured in their surveys [ 30 , 35 ]. Moreover, three of the eight studies [ 30 , 32 , 36 ] reported collecting only a pre-specified list of medications.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…38 The absence of accurate information about COVID-19 resulted in inaccurate self-medication in Uganda. 39 Furthermore, the consequences of panicking from COVID-19 extended to business including the stock market, and foreign trade, and increased the price of essentials, such as surgical masks and face masks, sanitizers, electronics, and electrical materials. 40 In Bangladesh, lack of coordination among government authorities resulted in miscommunication and misunderstanding of the measures that have been taken by the government.…”
Section: Dovepressmentioning
confidence: 99%
“…Studies characteristics are shown in Table 2. The eight included studies reported data on selfmedication practices in six different countries: three from Peru [30][31][32], one from Bangladesh [33], one from Togo [29], one from Nigeria [34], one from Uganda [35], and one from the Kingdom of Saudi Arabia [36]. All studies were cross-sectional.…”
Section: Studies Characteristicsmentioning
confidence: 99%